2018
DOI: 10.7759/cureus.2461
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic Resident Practice Management and Health Policy Education: Evaluation of Experience and Expectations

Abstract: IntroductionPractice management and health policy have generally not been considered integral to orthopaedic resident education. Our objective was to evaluate residents’ current experience and knowledge, formal training, and desire for further education in practice management and health policy.MethodsWe developed a 29-question survey that was divided into three sections: practice management, initial employment opportunity, and health policy. Within each section, questions were directed at a resident’s current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Although resources have improved over the years, there is still a gap in understanding medical coding and billing. 3 , 16 , 17 , 18 , 19 The ASSH offers a free webinar on practice management, which has included topics on reimbursement and coding. 20 Formal education programs have shown significant improvement in residents’ knowledge and ability to identify fraud.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although resources have improved over the years, there is still a gap in understanding medical coding and billing. 3 , 16 , 17 , 18 , 19 The ASSH offers a free webinar on practice management, which has included topics on reimbursement and coding. 20 Formal education programs have shown significant improvement in residents’ knowledge and ability to identify fraud.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has shown that these educational problems still persist. 3 , 16 , 17 , 18 , 19 The ASSH Coding Corner newsletter is an effort to distribute coding knowledge and updates across the ASSH membership. 20 Improved communication and education regarding appropriate coding practices as well as easily accessible reference materials may assist in minimizing coding discrepancies for surgical hand procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the practice setup (i.e., academics, private practice, or hospital-employed), knowing how to appropriately code and bill for services is critical. In a recent survey study by Stautberg et al, >90% of the responding orthopaedic residents agreed that training in coding and billing during residency is “essential” and their training would be more complete with formal education on these topics 8 . Only 13% of those respondents stated that they would be confident enough to code for provided services if they were in independent practice the next day 8 .…”
Section: Achieving Competence In Practice Managementmentioning
confidence: 99%
“…However, health policy and advocacy education have traditionally been lacking within US graduate medical education, with most non-medical educational efforts focusing on business preparedness and practice management among residents and recent graduates across many medical specialties. [1][2][3][4] These gaps in health policy and advocacy education can leave trainees feeling frustrated and paralysed; while trainees feel it is essential for physicians to participate in advocacy efforts to shape health policy, their perceived ability to do so is curtailed by a lack of knowledge surrounding these areas. 5 6 Further, lack of health policy and advocacy awareness can also be detrimental to the quality and equity of patient care provided, prompting calls to address this critical training gap.…”
Section: Introductionmentioning
confidence: 99%